Cleisostoma mulunense (Orchidaceae), a new species from Guangxi, China - Qin, Ying; Tan, Wei Ning; Luo, Liu Juan; Liu, Yan (Phytotaxa, 2023)
Cleisostoma mulunense, a new species of Orchidaceae from Mulun National Nature Reserve, Guangxi, China, is described and illustrated. It is close to C. menghaiense, but can be easily distinguished from the latter mainly by its yellowish green to yellow, with purplish brown flowers, suboblong dorsal sepal, broadly oblong and obviously oblique lateral sepals, oblong petals, lip median lobe with 2 basal backward triangular lobules, cylindroid spur. Detailed morphological descriptions, colour photographs and other information of the new species are provided.